ANALISIS INTENSITAS MEDAN MAGNET EXTREMELY LOW FREQUENCY (ELF) DI SEKITAR LAPTOP - Shanti Dewi Agustina; Sri Handono Budi Prasutowo; Sudarti Sudarti (JURNAL PEMBELAJARAN FISIKA, 2018)
Research on the analysis of the magnetic field intensity Extremely Low Frequency (ELF) around laptop is important method to prevent the impact of disease risks caused by electromagnetic field radiation and evaluation of the safety level of environmental radiation by magnetic field ELF. The instrument used to measure the magnetic field intensity EMR tester GM 3120 is capable of measuring magnetic fields start from 0,01-19,99 μT, the results of the intensity of exposure to magnetic fields measured by different power in six position and two condition (On and Stanby menuju Off). The distance of measurement is 30 cm. the distance is selected because it is based on the normal people’s eye reading distance. Results of correlation data are analyzed using correlation pearson by IBM SPSS Statistic 23. The result showed that the processor power by type was directly proportional with the magnetic field intensity. If power higher so magnetic field will be bigger, and if power lower so magnetic field will be smaller. The magnetic field intensity value on the Stanby menuju Off condition was decreased. The results showed the highest intensity of different magnetic fields on 13 laptop.Keywoards: Magnetic fiels intensity of ELF, laptop, condition, position.